Performance under sulfate attack of concrete additioned with fluid catalytic cracking catalyst residue (FCC) and metakaolin (MK) (2013)
In this work the evaluation of the performance of concrete added with Fluid Catalytic Cracking Catalyst residue (FCC) from a Colombian petroleum company, under sulfate attack, is presented. The results of this concrete are compared with the results of Metakaolin (MK) added concrete. The analysis of the pozzolanic materials included the determination of the particle size, the pozzolanic activity and the chemical and mineralogical composition. Different percentages of FCC were used as Portland cement replacement in proportions of 0, 10, 20 and 30%; similarly concrete added with 20% of MK as replacement was elaborated. Compressive strength and performance under sulfate attack were evaluated. Results showed that concrete with FCC and MK as well as control concrete had similar behavior; however its expansion was higher. In addition, the performance of the two types of concrete (FCC y MK) under sulfate attack was comparable; this could be due to fact that FCC and MK showed similarities regarding of their chemical and mineralogical composition. Importantly, after 360 days of exposure the specimens with MK and FCC showed no significant deterioration.